2017
DOI: 10.1021/jacs.6b11864
|View full text |Cite
|
Sign up to set email alerts
|

Urea Anions: Simple, Fast, and Selective Catalysts for Ring-Opening Polymerizations

Abstract: Aliphatic polyesters and polycarbonates are a class of biorenewable, biocompatible, and biodegradable materials. One of the most powerful methods for accessing these materials is the ring-opening polymerization (ROP) of cyclic monomers. Here we report that the deprotonation of ureas generates a class of versatile catalysts that are simultaneously fast and selective for the living ring-opening polymerization of several common monomers, including lactide, δ-valerolactone, ε-caprolactone, a cyclic carbonate, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
275
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 245 publications
(291 citation statements)
references
References 69 publications
15
275
1
Order By: Relevance
“…The series of compounds In(N(SiMe 3 ) 2 ) 3 ( 1 ), In(N(SiMe 3 ) 2 ) 2 Cl⋅THF ( 2 ) and In(N(SiMe 3 ) 2 )Cl 2 ⋅(THF) n ( 3 ) were prepared by minor modifications of the literature method involving a salt metathesis reaction of Na(N(SiMe 3 ) 2 ) and InCl 3 . In the case of compounds 2 and 3 crystallographic studies confirmed the formulations (Figure ).…”
Section: Methodsmentioning
confidence: 69%
“…The series of compounds In(N(SiMe 3 ) 2 ) 3 ( 1 ), In(N(SiMe 3 ) 2 ) 2 Cl⋅THF ( 2 ) and In(N(SiMe 3 ) 2 )Cl 2 ⋅(THF) n ( 3 ) were prepared by minor modifications of the literature method involving a salt metathesis reaction of Na(N(SiMe 3 ) 2 ) and InCl 3 . In the case of compounds 2 and 3 crystallographic studies confirmed the formulations (Figure ).…”
Section: Methodsmentioning
confidence: 69%
“…This approach was inspired by the use of monourea or bis(thio)urea catalysts in small molecule transformations . Neutral bisureas were readily prepared in one step from the commercially available isocyanates and bisamines at room temperature . The results of 1 H and 13 C NMR spectra, FTIR, element analysis confirmed the success synthesis of bisurea catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The thioimidate catalyst demonstrated good catalytic activity in lactide polymerization, but lower activity in TMC ROP and low productivity in polymerization of lactones. The novel simple and promising catalysts, the close structural analogs of TU-derived thioamidate, were studied in the few past years [138][139][140][141][142]. These catalysts, which represent the metal derivatives of disubstituted ureas, demonstrated high activities in ROP of cyclic esters of all actual structure types-lactide, lactones, TMC, and ethylene phosphates.…”
Section: Thiourea-based Catalystsmentioning
confidence: 99%